An unexpected pleasure eaudiobook - Camp, Candace (The Mad Morelands,, 2020)
Had Theo Moreland, the Marquess of Raine, killed her brother? And had the treasure the two men sought in South America hastened his descent to an early grave? American journalist Megan Mulcahey has to discover the truth. But to find out, she needs to infiltrate the marquess's household. The new American governess intrigues Theo. Wanderlust has always plagued him—until Miss Mulcahey comes to Broughton House to teach his young siblings. Now, the strange pull of their immediate desire both troubles and excites him. He's seen her beauty once before, in a fever dream his memory cannot escape. So why is this delicious vision now snooping around his mansion like a common thief? Contains mature themes.